ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PEDAGANG IKAN LAUT DI PASAR BATUSANGKAR Rahmad Diego, Zul Azhar, Ariusni - Rahmad Diego; Zul Azhar (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research purpose are to analyze the effect of capital, price, labor, and education level on the income of saltwater fish seller in Batusangkar’s Market. The kind of this research is descriptive’s research, the data used are primary data which are analyzed using Multiple Linear Regression. The result show that the capital has a positive and significant effect on the income of saltwater fish seller in Batusangkar’s Market and the price has a positive and significant effect on the income of saltwater fish seller in Batusangkar’s Market and the working hours has a positive and significant effect on the income of saltwater fish seller in Batusangkar’s Market and the education level has a positive and significant effect on the income of saltwater fish seller in Batusangkar’s Market and the capital, price, working hours, and education level has a positive and significant effect as together on the income of saltwater fish seller in Batusangkar’s Market.